2015
DOI: 10.1111/ggi.12681
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative muscle mass index as a predictor of skeletal muscle function deficit in Asian older adults

Abstract: Aim:The present cross-sectional study was carried out among community-dwelling Koreans to determine the validity of various muscle mass indices and to propose more clinically relevant diagnostic criteria.Methods: This study measured the anthropometrics, body composition and physical capability of 415 older Koreans. Skeletal muscle indices were calculated by dividing appendicular lean mass by height or weight. Apart from this, we adjusted appendicular lean mass for body mass index, body surface area or waist-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In our study, there was a significant difference in OS and DFS according to BSA when applying the log-rank test. In addition, BSA was correlated with PMA, as has been reported previously [28,30]. Therefore, we evaluated the clinical significance of PMA adjusted for BSA (PMA BSA ).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In our study, there was a significant difference in OS and DFS according to BSA when applying the log-rank test. In addition, BSA was correlated with PMA, as has been reported previously [28,30]. Therefore, we evaluated the clinical significance of PMA adjusted for BSA (PMA BSA ).…”
Section: Discussionmentioning
confidence: 74%
“…In our study, PMA BSA was a significant prognostic factor for both OS and DFS using the multivariate Cox model. Similarly, Chang also found that appendicular lean mass adjusted for BSA was more accurate in predicting low muscle function than are height squared- and weight-adjusted indices 30 . Because there is no available study on the clinical significance of PMA BSA in gastrointestinal tumors, further studies on the value of PMA BSA is needed for validation of our findings.…”
Section: Discussionmentioning
confidence: 88%
“…Receiver operating characteristic (ROC) curves were used to determine the optimal cutoff values for the PNI, NLR, PLR, and LMR. The lowest quartile was used as the cutoff value for the LBMI [25,26], because no standard reference value was available. The associations between different clinicopathological and nutritional parameters and the one year mortality rate were analyzed by Cox proportional hazard models by applying predefined cut-off values.…”
Section: Discussionmentioning
confidence: 99%
“…Since no in-hospital mortality happened in the female cohort in our database, we performed receiver operating characteristic (ROC) curve analysis by taking the rate of major complications as an indicator for predictive validity to determine the optimal cutoff value of TPAI in both sexes. 8,15 Then, we defined "CT-determined sarcopenia" or "TPAI-defined sarcopenia" as less than and equal to the cut-off value of TPAI which we calculated in this study. Meanwhile, we took 24.0 kg/m 2 as the diagnosis criteria of overweight, and 28 kg/m 2 as the diagnosis criteria of obesity in the Chinese population.…”
Section: Ct Image Analysis and Ct-determined Sarcopenia Definitionmentioning
confidence: 99%